2013
DOI: 10.7243/2052-6199-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and its derivatives in breast cancer: Current developments and potential for the treatment of drug-resistant cancers

Abstract: Curcumin, a spice found in curry powder, is receiving considerable attention as a possible chemopreventative and chemotherapeutic. This review considers the evidence for the use of curcumin as a treatment for breast cancer, particularly triple negative breast cancers (lacking ER, PR and HER2) which are resistant to many current treatments. Evidence suggests that curcumin suppresses the growth of breast cancers both in vitro and in vivo. In ER-cell lines curcumin causes apoptosis via a range of mechanisms at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…The central diketones form stable enols or are easily deprotonated and form enolates, while the α-and β-unsaturated carbonyl is a Michael acceptor and (19). The phenolic methoxy groups, as well as the ketone and enol groups, present on the ends and in the middle of the molecule, respectively, can participate in strong hydrogen bonding interactions (57).…”
Section: Discussionmentioning
confidence: 99%
“…The central diketones form stable enols or are easily deprotonated and form enolates, while the α-and β-unsaturated carbonyl is a Michael acceptor and (19). The phenolic methoxy groups, as well as the ketone and enol groups, present on the ends and in the middle of the molecule, respectively, can participate in strong hydrogen bonding interactions (57).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is, of course, the exception. A recent review on breast cancer by Cridge, Larsen and Rosengren summarizes associated molecular targets and points out the intervention of cytokines, growth factors, apoptosis and cell cycle proteins in addition to transcription factors and enzymes for a subset of MACs [ 32 ]. A recent modest kinase screen demonstrated that one MAC, EF31 ( 7a = 14 , X = NH, Y = N, Figure 2 ), is able to block 22 of 50 cancer-related kinases and suggests a mechanism dominated by competition with ATP [ 26 ].…”
Section: Cancer Mediation In Vitro and mentioning
confidence: 99%
“…Other reasons for turning from 1 to MACs are ease of synthesis [ 22 , 23 ] selectivity [ 9 , 24 , 25 ] and recognition that the pleiotropic nature [ 26 ] of the curcumin-like architecture permits rapid evaluation of drug potential for currently troublesome disorders such as highly resistant bacteria, Alzheimer’s syndrome, HIV, tuberculosis, malaria and diabetes [ 22 , 27 ]. Several excellent reviews detailing the diversity, applications and biological foundations of MACs for utility in human disease have appeared in the recent past [ 10 , 22 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides being used as an adjuvant in breast cancer chemotherapy, curcumin is able to regulate many signalling targets and has been used to augment targeted therapy sensitization (17). The therapeutic benefit of curcumin as a clinical drug, however, remains a challenge due to its poor bioavailability (18,19). Various concerns have been raised regarding the efficacy of curcumin against cancer (20)(21)(22).…”
mentioning
confidence: 99%